Regulation of biomolecular condensates by interfacial protein clusters - Folkmann, Andrew W; Putnam, Andrea; Lee, Chiu Fan; Seydoux, Geraldine (Science (American Association for the Advancement of Science), 2021)
Biomolecular condensates are cellular compartments that can form by phase separation in the absence of limiting membranes. Studying the P granules of , we find that condensate dynamics are regulated by protein clusters that adsorb to the condensate interface. Using in vitro reconstitution, live observations, and theory, we demonstrate that localized assembly of P granules is controlled by MEG-3, an intrinsically disordered protein that forms low dynamic assemblies on P granules. Following classic Pickering emulsion theory, MEG-3 clusters lower surface tension and slow down coarsening. During zygote polarization, MEG-3 recruits the DYRK family kinase MBK-2 to accelerate spatially regulated growth of the P granule emulsion. By tuning condensate-cytoplasm exchange, interfacial clusters regulate the structural integrity of biomolecular condensates, reminiscent of the role of lipid bilayers in membrane-bound organelles.